Transverse skeletal base adaptations with Bionator therapy: A pilot implant study - Araujo, A. M.; Buschang, P. H.; Melo, ACM (Mosby, Inc, 2004)
The purpose of this randomized, controlled trial was to evaluate transverse skeletal base adaptations to Bionator therapy. The sample included 25 patients (15 male, 10 female) aged 6.9 to 11.2 years with Class II Division 1 malocclusion. The patients were randomly allocated to either a control (n = 11) or treatment (n = 14) group and followed longitudinally for approximately 12 months. Treatment consisted of a Bionator only, constructed to remain approximately 2 mm from the buccal dentition. Transverse maxillary and mandibular changes were evaluated cephalometrically according to 4 bilateral maxillary and 2 bilateral mandibular implants. Untreated Class II controls exhibited significant increases between posterior maxillary implants but no significant changes between the anterior maxillary or mandibular implants. There were no significant width differences between the control and treated groups before treatment. Posterior maxillary implant widths increased significantly (P < .05) in both groups, but the treated group showed significantly greater width increases than the control group. The treated group also showed greater increases between mandibular implants, but the differences were not statistically significant. These results suggest that transverse skeletal base adaptations occur as a result of Bionator therapy.